The Effect of Wordwall Learning Media on Cognitive Abilities in Understanding Geometric Shapes in Group B - Suhaebatul Faoziyah; Gunawan Gunawan; Filsa Era Sativa (Indonesian Journal of Elementary and Childhood Education, 2026)
This study investigated the effect of using Wordwall as a learning medium on the cognitive abilities of kindergarten children in Mataram, specifically their understanding of geometric shapes. Employing a quantitative approach with a pre-experimental design (one-group pretest-posttest model), the study collected data through participant observation and documentation from 32 children in Group B. Parametric statistics, specifically a paired-samples t-test, were used for data analysis and hypothesis testing. The results revealed a significant improvement in cognitive abilities. The average pretest scores were 70.09 (B1), 76.27 (B2), and 76.70 (B3), which significantly increased in the posttest to 86.54 (B1), 89.81 (B2), and 88.20 (B3). Overall, the average pretest score for the sample was 74.28, improving to an average posttest score of 87.18. The paired-samples t-test yielded a Sig. (2-tailed) value of 0.001 (p < 0.05), confirming a statistically significant difference between pretest and posttest results after the intervention with Wordwall. These findings indicate that the use of Wordwall as a learning medium effectively improves the cognitive ability to understand geometric shapes in early childhood education.